Sensitization to inhaled and food allergen sources in patients with allergic diseases in Eastern China - Zhibang Hu; Zhibang Hu; Chunhui Wang; Jianrong Xue; Shiyu Yang; Yongzheng Bao; Yunhui Wu; Xiaoju Hou; Yishake Kaiseer; Jing Ma (Frontiers in Allergy)
BackgroundAllergen exposure plays a critical role in the onset of allergic disease, and the distribution of allergens varies by geographic location, climate, and lifestyle.MethodsA retrospective analysis was conducted on the data of 4,149 patients with clinically suspected allergic diseases who sought medical care at Changzhou Third People's Hospital. The total IgE and specific IgE (sIgE) levels for 19 inhaled and food allergen sources were assessed using the Mediwiss AllergyScreen system. The sensitization patterns to various allergen sources were delineated based on sex and age categories.ResultsA total of 2,491 (60.04%) patients were positive for sIgE to at least one allergen source. Specifically, 997 (40.02%) patients were positive for one allergen source, while 1,494 (59.98%) were positive for two or more allergen sources. The sensitization rate for inhaled allergen sources was 49.41% (2,050), which was significantly higher than that for food allergen sources at 36.61% (1,519) (p < 0.05). The most commonly inhaled allergen source was D. pteronyssinus (37.58%, 1,559/4,149), followed by mold mix (13.11%, 544/4,149) and house dust (9.11%, 378/4,149). Among food allergen sources, the most prevalent reactions were cashew nut (15.57%, 646/4,149), cow's milk (10.99%, 456/4,149), and egg (9.33%, 387/4,149). The majority of sIgE levels were concentrated in the lower grades (grade I to III), while eight cases of crab and six cases of shrimp allergen sources presented at the highest responses (grade IV). Males exhibited significantly higher sIgE-positive rates for both inhaled and food allergen sources than females (p < 0.05). Additionally, the sIgE-positive rates for most inhaled and food allergen sources displayed significant variations across different age groups (p < 0.05). The highest sIgE-positive rate for inhaled allergen sources was observed in the 11–15 years group, and the positive rates of sIgE for food allergen sources decreased with advancing age. The levels of total serum IgE also varied among different age groups, with 2,631 (63.41%) individuals belonging to the high-concentration group. Total serum IgE exhibited an upward trend until the age of 11–15 years, which was then followed by a steady decrease.ConclusionThe results revealed the sensitization characteristics of allergen sources in eastern China, providing valuable insights into the prevention, diagnosis, and management of allergic diseases in this region.